Children’s perceptions of scientists, and of themselves as scientists - Dickson, Martina; McMinn, Melissa; Cairns, Dean; Osei-Tutu, Sharon (LUMAT: International Journal on Math, Science and Technology Education, 2021)
In rapidly developing countries such as the United Arab Emirates (UAE), where this study took place, having a body of competent, dedicated key workers in STEM fields is critical to growing national economies. This, in turn, requires motivated, well-qualified graduates of STEM degrees. School students’ perceptions of science, scientists and science careers have been shown in some research to affect uptake of science degrees later on. How much of their science classwork students experience as authentically ’feeling like scientists’ is less understood, yet important. This study took place in upper primary science classrooms in the UAE. Immediately following a science lesson, children were interviewed in focus groups (n=66, with an approximately even gender split). Broad questions were explored, such as whether they felt like ’real scientists’ when they ’performed’ science in the classroom, whether they enjoyed science, and their science career aspirations. 83% of students stated enjoying science, while 61% would like to have a career involving science in the future. The interview data revealed that, overall, children mostly disagreed that their classroom science was reflective of work a ’real scientist’ would do, chiefly due to perceptions of a lack of discovery element in their work, which suggested to them a lack of authentic science exploration, and of the work not being dangerous enough. Students frequently reported feeling that they were ’following steps’ because the teacher ’already knew the answers’, which was different from the work of a scientist. The implications of these findings to classroom practice are discussed.